Species delimitation in the Populus laurifolia complex (Salicaceae) based on phylogenetic and morphometric evidence - Wei, Xueya; Cui, Xingyong; Yuan, Fulin; Zhou, Kerou; Zhou, Liwei; Zhao, Changli; Guo, Shaoyu; Shang, Ce; Zhang, Zhixiang (Frontiers in Plant Science, 2025)
Due to significant morphological differences and extensive interspecific hybridization, there are numerous species complexes with taxonomic challenges in the genus Populus. Integrative taxonomy, which combines evidence of morphology, molecular phylogeny, niche differentiation, and reproductive isolation, provides the most effective approaches for species delimitation. The Populus laurifolia complex, which belongs to Populus subg. Tacamahaca (Salicaceae), is distributed in the Altai Mountains and Tianshan Mountains. This complex exhibits morphological variability, making species delimitation challenging. Due to limited sampling and systematic studies, its taxonomy has remained unresolved. In this study, 337 specimens, along with online digital samples representing nearly all wild populations, were collected. Morphological analyses were performed to evaluate key traits and clarify species boundaries. Phylogenetic relationships were reconstructed using concatenation and coalescent methods based on 566,375 nuclear single-nucleotide polymorphisms (SNPs). Ecological niche differentiation was assessed, and ABBA–BABA analysis was used to examine interspecific hybridization. The results revealed that this complex, based on a series of significant character states, could be morphologically distinguished into three species—P. laurifolia (Populus pilosa considered a synonym of P. laurifolia), Populus talassica, and Populus pamirica—which also correspond to three well-supported clades in the phylogenetic trees. P. pamirica exhibits some degree of ecological niche differentiation from P. talassica and P. laurifolia, whereas the latter two show minimal differentiation. Gene flow within the complex remains limited. This research underscores the importance of integrating multiple lines of evidence in the classification of Populus, providing a framework for future taxonomic studies.